2013
DOI: 10.1177/0004867413506754
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional family environment in affected versus unaffected offspring of parents with bipolar disorder

Abstract: Families with a BD parent presented more dysfunctional interactions among members. Moreover, the presence of BD or other psychiatric disorders in the offspring of parents with BD is associated with higher levels of control. These results highlight the relevance of psychosocial interventions to improve resilience and family interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 33 publications
1
20
0
3
Order By: Relevance
“…Greater exposure to independent life events in OBD indicates that they were more likely to be exposed to stressors in which they did not have a direct role. This finding is in agreement with previous studies indicating greater conferred risk in adolescents with a parent with BD and with less family cohesion, 3133 and may indicate need for early intervention to assist parents with BD in reducing environmental stressors for their offspring. The relationship between greater frequency of independent stressful life events and proband comorbid SUD for OBD is also worth noting.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Greater exposure to independent life events in OBD indicates that they were more likely to be exposed to stressors in which they did not have a direct role. This finding is in agreement with previous studies indicating greater conferred risk in adolescents with a parent with BD and with less family cohesion, 3133 and may indicate need for early intervention to assist parents with BD in reducing environmental stressors for their offspring. The relationship between greater frequency of independent stressful life events and proband comorbid SUD for OBD is also worth noting.…”
Section: Discussionsupporting
confidence: 93%
“…Impaired family function and lower cohesion negatively impact outcome in youth BD, in particular. 33,38 Previous studies also have indicated greater risk for mood disorder in offspring exposed to parental BD, and a role for intervention in families with a bipolar parent. 39 In particular, comorbid SUD in BD probands was associated with a greater number of independent stressful life events for offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Families of children at risk and who actually have BPSD show dysfunctional interactions, including high levels of: conflict (Barron et al, 2014; Belardinelli et al, 2008; Chang, Blasey, Ketter, & Steiner, 2001; Ferreira et al, 2013; Nader et al, 2013); control (Ferreira et al, 2013; Nader et al, 2013); aggression (Keenan-Miller et al, 2012); quarreling (Schenkel, West, Harral, Patel, & Pavuluri, 2008); forceful punishment (Schenkel et al, 2008); parental tension (Nader et al, 2013); and negative expressed emotion (Nader et al, 2013). These families also demonstrate low levels of: warmth, affection, and intimacy (Schenkel et al, 2008); cohesion (Belardinelli et al, 2008; Chang et al, 2001; Ferreira et al, 2013; Nader et al, 2013); expressiveness (Barron et al, 2014; Belardinelli et al, 2008); organization (Barron et al, 2014; Belardinelli et al, 2008; Chang et al, 2001; Ferreira et al, 2013; Nader et al, 2013); intellectual-cultural orientation (Barron et al, 2014; Belardinelli et al, 2008; Ferreira et al, 2013); active-recreational orientation (Barron et al, 2014; Belardinelli et al, 2008; Ferreira et al, 2013); moral-religious emphasis (Ferreira et al, 2013); and positive expressed emotion (Nader et al, 2013). In addition, worse longitudinal course of BPSD is predicted by impaired family characteristics, such as: low maternal warmth (Geller et al, 2008); chronic stress in family, romantic, and peer relationships (Kim, Miklowitz, Biuckians, & Mullen, 2007; Siegel et al, 2015); frequency and severity of independent family stressful life events (Kim et al, 2007); low levels of cohesion and adaptability (Sullivan, Judd, Axelson, & Miklowitz, 2012); and high levels of conflict (Sullivan et al, 2012).…”
Section: Families Of Children With Bpsdmentioning
confidence: 99%
“…), and on the symptomatic and functional recovery of patients with BPD (Ferreira et al . ; McCann et al . ; Reinares et al .…”
Section: Discussionmentioning
confidence: 99%
“…A poorly‐functioning family has been associated with severe psychopathology and low psychosocial functioning in patients with BPD (Ferreira et al . ; Sullivan et al . ).…”
Section: Introductionmentioning
confidence: 99%